The Impact of Generation Z’S Perception, Buying Interest, and Social Media Towards Purchase Decision in Cinema XXI Ticket Sales Over the Years - Cecilia Endra; Felicia Angelina Tantono; Jerica Alverina; Putri Nadia Vanessa; Veriessa (International Journal of Economics, Business Management and Accounting (IJEBMA), 2020)
The abstract of "The Impact of Generation Z’s Perception, Buying Interest, and Social Media Towards Purchase Decision in Cinema XXI Ticket Sales Over the Years" provides an overview of a study that explores the relationships between Generation Z's perception, buying interest, social media engagement, and their purchase decisions regarding Cinema XXI ticket sales. Through a quantitative research approach, data was collected using surveys distributed among Generation Z individuals. The study employed validated scales to assess Generation Z's perception of the cinema, their buying interest, social media usage patterns, and how these factors influence their decisions to purchase Cinema XXI tickets. Statistical techniques, including regression analysis, were employed to analyze the data and determine the impact of these factors on purchase decisions. Ethical considerations were upheld in the research process. The findings contribute to a deeper understanding of Generation Z's behavior in relation to cinema ticket purchases, although potential limitations stem from the representativeness of the sample and self-reported data. Nevertheless, the study offers valuable insights for Cinema XXI's marketing strategies and audience engagement efforts